НАРОДНАЯ ЗАГАДКА СКВОЗЬ ПРИЗМУ ЛОГИЧЕСКОГО АНАЛИЗА - Kamalova, Alla (Acta Neophilologica, 2015)
This article provides the logical description of a folklore riddle (737 riddles). Research problems are solved with the help of the static, semantic and stylistic analyses. The figurative system of riddles about a firmament is discussed and cognitive structures are studied. The author additionally commentson the national ideas on cosmism.